2015
DOI: 10.1080/09168451.2015.1006571
|View full text |Cite
|
Sign up to set email alerts
|

A putative porin gene of Burkholderia sp. NK8 involved in chemotaxis toward β-ketoadipate

Abstract: Burkholderia sp. NK8 can utilize 3-chlorobenzoate (3CB) as a sole source of carbon because it has a megaplasmid (pNK8) that carries the gene cluster (tfdT-CDEF) encoding chlorocatechol-degrading enzymes. The expression of tfdT-CDEF is induced by 3CB. In this study, we found that NK8 cells were attracted to 3CB and its degradation products, 3- and 4-chlorocatechol, and β-ketoadipate. Capillary assays revealed that a pNK8-eliminated strain (NK82) was defective in chemotaxis toward β-ketoadipate. The introduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…The chemotactic behavior of strain NH9 towards aromatic compounds was tested in semi-solid agar plate assays [71]. For these assays, 100 ml NH9 cell culture in the early stationary phase (O.D.…”
Section: Semi-solid Agar Plate Assaysmentioning
confidence: 99%
“…The chemotactic behavior of strain NH9 towards aromatic compounds was tested in semi-solid agar plate assays [71]. For these assays, 100 ml NH9 cell culture in the early stationary phase (O.D.…”
Section: Semi-solid Agar Plate Assaysmentioning
confidence: 99%
“…NK8 can degrade 3-chlorobenzoate (3CB), an intermediate of polychlorinated biphenyls, via the chlorocatechol ortho -cleavage pathway encoded by the tfdCDEF genes ( 2 ). We previously demonstrated that NK8 cells are motile and exhibit chemotaxis toward 3CB and its degradation products ( 3 ).…”
Section: Announcementmentioning
confidence: 99%
“…The genes for the conversion of 3CB to 3- and 4-chlorocatechols ( cbeABCD ) were located on pNK81. The tfdCDEF genes (NK8_82450 to NK8_82480) ( 2 ) were on pNK84 along with the putative DNA relaxase gene traI (NK8_85450) ( 3 ), suggesting that the tfdCDEF genes were acquired by horizontal transfer. The genus Caballeronia has recently been divided from the genus Burkholderia ( 11 ).…”
Section: Announcementmentioning
confidence: 99%
See 1 more Smart Citation